2019
DOI: 10.1108/jcm-11-2017-2428
|View full text |Cite
|
Sign up to set email alerts
|

Sharing of branded viral advertisements by young consumers: the interplay between personality traits and ad appeal

Abstract: Purpose This study aims to investigate the influence of Big Five Personality traits (i.e. openness to experience, conscientiousness, extraversion, agreeableness and neuroticism) on young consumers’ intentions to share branded viral video advertisements. Further, this study also demonstrates that the advertising appeal (informational versus emotional) used in the viral advertisement moderates the effects of specific personality traits on the sharing of viral ads. Design/methodology/approach A conceptual frame… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 54 publications
0
9
0
1
Order By: Relevance
“…Participants reported higher emotional ratings in the emotional appeal condition (M emotional = 5.64 vs. M rational = 4.73; F[1, 267] = 19.89, p < .001), and higher rational ratings for rational appeal (M emotional = 5.29 vs. M rational = 5.67; F[1, 267] = 5.42, p < .05). Collapsing the scores of emotionality and rationality in one scale (e.g., Kulkarni et al, 2019), we also found there was a significant difference with regard to the ad appeal, which implies participants rated the emotional appealing ad more emotional (M = 4.17, SD = .85) and the rational appealing ad as more rational (M = 3.53, SD = .87), t(267) = 6.18, p < 0.001.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Participants reported higher emotional ratings in the emotional appeal condition (M emotional = 5.64 vs. M rational = 4.73; F[1, 267] = 19.89, p < .001), and higher rational ratings for rational appeal (M emotional = 5.29 vs. M rational = 5.67; F[1, 267] = 5.42, p < .05). Collapsing the scores of emotionality and rationality in one scale (e.g., Kulkarni et al, 2019), we also found there was a significant difference with regard to the ad appeal, which implies participants rated the emotional appealing ad more emotional (M = 4.17, SD = .85) and the rational appealing ad as more rational (M = 3.53, SD = .87), t(267) = 6.18, p < 0.001.…”
Section: Methodsmentioning
confidence: 99%
“…Such targeting technology paired with sizable user growth allowed social media advertising to become more prominent, prompting an increased need for additional research. Previous research on personality and social media identified how personality segments Facebook users (Ryan & Xenos, 2011), influences user motivations for Facebook usage (Seidman, 2013), and predicts a consumers' likelihood of sharing viral advertisements (Kulkarni, Kalro, & Sharma, 2019). While previous studies have explored the effects of personality in general social media use, research should now examine specific contexts of social media advertising since different personality traits are associated with diverse behavioral contexts and outcomes (e.g., Anglim & O'Connor, 2019; De Vries, De Vries, De Hoogh, & Feij, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Some investigations have found the differences between attitudes and consumer preferences in online or offline settings (Kwon and Lennon, 2009; Molina et al , 2017). Furthermore, it is established that young consumers prefer an online environment (Kulkarni et al , 2019; Prasad et al , 2019). Additionally, young consumers are ready to pay more for eco-friendly products and prefer to buy from eco-friendly packaging companies (Prakash and Pathak, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Digital advertising refers to the distribution of advertising content by identified sponsors in interactive digital platforms (Kulkarni et al, 2019). Some of the factors that have contributed to digital media's popularity are technology, globalization, and consumers' increased use of social media.…”
Section: Introductionmentioning
confidence: 99%